Antimicrobial Peptides With Antibiofilm Activity Against Xylella fastidiosa - Moll, Luís; Badosa, Esther; Planas, Marta; Feliu, Lidia; Montesinos, Emilio; Bonaterra, Anna (Frontiers in Microbiology, 2021)
Xylella fastidiosa is a plant pathogen that was recently introduced in Europe and is causing havoc to its agriculture. This Gram negative bacterium invades the host xylem, multiplies and forms biofilm occluding the vessels and killing its host. In spite of the great research effort there is no method that effectively prevents or cure hosts from infections. The main control strategies up to now are eradication, vector control and pathogen-free plant material. Antimicrobial peptides have arisen as promising candidates to combat this bacterium due to their broad spectrum of activity and low environmental impact. In this work peptides previously reported in the literature and newly designed analogues were studied for its bactericidal and antibiofilm activity against X. fastidiosa. Also, their hemolytic activity and effect on tobacco leaves when infiltrated were determined. To assess the activity of peptides, the strain IVIA 5387.2 with moderate growth, able to produce biofilm and susceptible to antimicrobial peptides was selected among six representative strains found in the Mediterranean area (DD1, CFBP 8173, Temecula, IVIA 5387.2, IVIA 5770 and IVIA 5901.2). Two interesting groups of peptides were identified with bactericidal and/or antibiofilm activity and low-moderate toxicity. The peptides 1036 and RIJK2 with dual (bactericidal-antibiofilm) activity against the pathogen and moderate toxicity stand out as the best candidates to control X. fastidiosa diseases. Nevertheless, peptides with only antibiofilm activity and low toxicity are also promising agents as they could prevent the occlusion of xylem vessels caused by the pathogen. The present work contributes to provide novel compounds with antimicrobial and antibiofilm activity that could lead to the development of new treatments against diseases caused by X. fastidiosa